1997
DOI: 10.1152/ajpgi.1997.272.5.g1186
|View full text |Cite
|
Sign up to set email alerts
|

Female rats exhibit greater susceptibility to early alcohol-induced liver injury than males

Abstract: It is known that women develop hepatic injury more rapidly and with exposure to less ethanol than men; however, mechanisms remain unclear. The purpose of this study was to determine if an enteral alcohol delivery model could be used to study susceptibility of females to alcohol-induced liver injury. Male and female Wistar rats (age- or weight-matched) were given ethanol (11-12 g.kg-1.day-1) continuously for up to 4 wk via intragastric feeding, and control rats received a high-fat diet without ethanol. There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
105
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 0 publications
12
105
4
Order By: Relevance
“…30 However, the levels of circulating endotoxin that were needed (200-500 pg/mL) were 20 to 50 times higher than those found in our ethanol-treated animals (mean, 9.3 pg/mL) and 6 to 10 times higher than after ethanol feeding by the intragastric model (30-70 pg/mL). 8,31 Remarkably, this dose of endotoxin did not significantly enhance steatosis and focal inflammation in ethanol-fed animals. Previous studies, based on both animal experiments 8,31 and clinical observations, 4 have suggested aggravation of ALD by circulating endotoxin.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…30 However, the levels of circulating endotoxin that were needed (200-500 pg/mL) were 20 to 50 times higher than those found in our ethanol-treated animals (mean, 9.3 pg/mL) and 6 to 10 times higher than after ethanol feeding by the intragastric model (30-70 pg/mL). 8,31 Remarkably, this dose of endotoxin did not significantly enhance steatosis and focal inflammation in ethanol-fed animals. Previous studies, based on both animal experiments 8,31 and clinical observations, 4 have suggested aggravation of ALD by circulating endotoxin.…”
Section: Discussionmentioning
confidence: 83%
“…8,31 Remarkably, this dose of endotoxin did not significantly enhance steatosis and focal inflammation in ethanol-fed animals. Previous studies, based on both animal experiments 8,31 and clinical observations, 4 have suggested aggravation of ALD by circulating endotoxin. Endotoxin by itself caused occasional polymorphic inflammation, particularly in the sinusoids.…”
Section: Discussionmentioning
confidence: 83%
“…Plasma endotoxin levels were more than 2-fold higher in females than males following ethanol feedng and ICAM-1 expression in hepatic endothelial cells was also about 2-fold greater in females than males. Thus, a new model to study female susceptibility to alcoholic hepatitis has been developed (13). Initial work with this model fits the idea that endotoxin and Kupffer cells are responsible for the increased susceptibility of women to alcohol compared to men.…”
Section: Gender Studiesmentioning
confidence: 99%
“…Radical adducts are substituted nitroxide free radicals, which tend to be relatively long-lived compared to free radicals which are very transient in biological systems. POBN radical adducts characteristically exhibit a six-line ESR spectrum (figure 1A), while 13 C substitution on the alpha-carbon of a spin-trapped species causes six additional lines due to the magnetic interaction of the 13 C with the unpaired electron. The subsequent production of a 12-line spectrum after administration of 13 C ethanol provides unequivocal physical evidence that the trapped radical arises from the labeled parent ethanol.…”
Section: Free Radicalsmentioning
confidence: 99%
See 1 more Smart Citation